Eksplorasi Pola Berpikir Kreatif Siswa dalam Pemecahan Masalah Matematika Berbasis Computational Thinking - Wahyuni, Dewi; Budi Antoro (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2025)
The abstract should describe clearly the content of paper, and should provide a brief introduction to the problem, objective of paper, followed by a statement regarding the methodology and a brief summary of results. Abstracts are written in a single paragraph, 10pt Book Antiqua, no more than 200 words. This study aims to explore students' creative thinking patterns in solving mathematics problems based on Computational Thinking (CT). CT is a thinking approach that involves decomposition, pattern recognition, abstraction, and algorithmic thinking, enabling students to solve problems systematically and efficiently. This research employs an exploratory qualitative method with purposive sampling of five twelfth-grade students at SMK Samudera Indonesia. Data were collected through problem-solving tests, observations, interviews, and worksheet analysis. The findings indicate that students with a high level of creative thinking can effectively apply CT concepts, particularly in decomposition and abstraction. Meanwhile, students with a moderate level of creative thinking still require examples and guidance in recognizing patterns and structuring solutions systematically. The main challenges identified include difficulties in understanding the fundamental concepts of sequences and series, reliance on formulas without deep comprehension, and a lack of confidence in trying different approaches. These findings suggest that incorporating Computational Thinking in mathematics learning can enhance students' creativity in problem-solving while also developing a more logical and systematic mindset.